Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 3rd ACM Workshop on Information Hiding and Multimedia Security 2015
DOI: 10.1145/2756601.2756603
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sequential Fingerprinting

Abstract: We study sequential collusion-resistant fingerprinting, where the fingerprinting code is generated in advance but accusations may be made between rounds, and show that in this setting both the dynamic Tardos scheme and schemes building upon Wald's sequential probability ratio test (SPRT) are asymptotically optimal. We further compare these two approaches to sequential fingerprinting, highlighting differences between the two schemes. Based on these differences, we argue that Wald's scheme should in general be p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Dynamic settings. For streaming applications [14,22,26,41], decisions on whether to accuse users or not need to be made in realtime as well. As the NNS techniques considered here commonly rely on static data, it is not directly obvious whether the same speedups can be obtained when the data arrives in a streaming fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic settings. For streaming applications [14,22,26,41], decisions on whether to accuse users or not need to be made in realtime as well. As the NNS techniques considered here commonly rely on static data, it is not directly obvious whether the same speedups can be obtained when the data arrives in a streaming fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, past work has shown that joint decoders achieve superior performance to simple decoders [2,7,11,17,18,21,23,30], but are often considered infeasible due to their high decoding complexity. Moreover, in dynamic settings [22,26] where decisions about the accusation of users need to be made swiftly, an efficient decoding method is even more critical. Techniques that can speed up the decoding procedure may therefore be useful for further improving these schemes in practice.…”
Section: Related Workmentioning
confidence: 99%